Evaluation of an experiential training program in patient-centered outcomes and comparative effectiveness research for diverse researcher communities and health care organizations. Issue 1 (15th March 2023) - Buchwald, Dedra S.; Rogers, Megan H.; Rose, Barbara A.; Bresnahan, Brian W.; Devine, Beth; LeResche, Linda; Nelson, Lonnie A.; Patrick, Donald L.; Lavallee, Danielle C.; Garrison, Michelle M.; White, Andrew A.; Kessler, Larry G.
Abstract: Background/Objective: The goal of the Patient-Centered Outcomes Research Partnership was to prepare health care professionals and researchers to conduct patient-centered outcomes and comparative effectiveness research (CER). Substantial evidence gaps, heterogeneous health care systems, and decision-making challenges in the USA underscore the need for evidence-based strategies. Methods: We engaged five community-based health care organizations that serve diverse and underrepresented patient populations from Hawai'i to Minnesota. Each partner nominated two in-house scholars to participate in the 2-year program. The program focused on seven competencies pertinent to patient-centered outcomes and CER. It combined in-person and experiential learning with asynchronous, online education, and created adaptive, pragmatic learning opportunities and a Summer Institute. Metrics included the Clinical Research Appraisal Inventory (CRAI), a tool designed to assess research self-efficacy and clinical research skills across 10 domains. Results: We trained 31 scholars in 3 cohorts. Mean scores in nine domains of the CRAI improved; greater improvement was observed from the beginning to the midpoint than from the midpoint to conclusion of the program. Across all three cohorts, mean scores on 52 items (100%) increased (p ≤ 0.01), and 91% of scholars reported the program improved their skills moderately/significantly. Satisfaction with the program was high (91%). Conclusions: Investigators that conduct patient-centered outcomes and CER must know how to collaborate with regional health care systems to identify priorities; pose questions; design, conduct, and disseminate observational and experimental research; and transform knowledge into practical clinical applications. Training programs such as ours can facilitate such collaborations.